Obstructive Sleep Apnea Syndrome, Objectively Measured Physical Activity and Exercise Training Interventions: A Systematic Review and Meta-Analysis - Mendelson, Monique; Bailly, Sébastien; Marillier, Mathieu; Flore, Patrice; Borel, Jean Christian; Vivodtzev, Isabelle; Doutreleau, Stéphane; Verges, Samuel; Tamisier, Renaud; Pépin, Jean-Louis (Frontiers in Neurology, 2018)
A systematic review of English and French articles using Pubmed/Medline and Embase included studies assessing objectively-measured physical activity levels of OSA patients and exploring the effects of exercise training on OSA severity, body mass index, sleepiness and cardiorespiratory fitness (VO2peak). Two independent reviewers analysed the studies, extracted the data and assessed the quality of evidence. For objectively-measured physical activity levels, 8 studies were included. The mean number of steps per day across studies was 5,388 (95% CI: 3,831 to 6,945; p<0.001), which was by far lower than the recommended threshold of 10,000 steps per day. For exercise training, 6 randomized trials were included. There was a significant decrease in apnea-hypopnea-index following exercise training (mean decrease of 8.9 events/h; 95% CI: -13.4 to -4.3; p<0.01), which was accompanied by a reduction in subjective sleepiness, an increase in VO2peak and no change in BMI. OSA patients present low levels of physical activity and exercise training is associated with improved outcomes. Future interventions (including exercise training) focusing on increasing physical activity levels may have important clinical impacts on both OSA severity and the burden of associated co-morbidities. Objective measurement of physical activity in routine OSA management and well-designed clinical trials are recommended.